Benefits of Using Social Media and Product Quality to Consumer Buying Interest in MSME Products in Griya Martubung Large Village Medan Labuhan District During the Covid-19 Pandemic - Nel Arianty; Muhammad Affan Ghifari Siregar (Journal of International Conference Proceedings (JICP), 2021)
The purpose of this research is to see and find out social media influence and product quality on consumer purchase interest in products MSME in Griya Martubung village, Medan Labuhan subdistrict Covid-19 pandemic. The type of research used is research using quantitative associative. This study has a population off all buyers who have bought MSME products in Griya Martubung village Medan Labuhan subdistrict whose number is unknown. Samples that worn with something study 120 respondents. Data collection technique use a questionnaire which has seen the results of the validity and reliability. Data analysis technique using multiple linear regression, classical assumption test, in the form of normality test, test multicollinearity, and heteroscedasticity test, t test (partial), F test (simultaneous), and coefficient of determination. The results of the multiple regression equation Y = 6.943 + 0.571 X1 + 0.243 X2. Results t test (partial) shows social media and product quality partially influence on consumer buying interest on MSME products in Urban village Griya Martubung, Medan Labuhan district during the Covid-19 pandemic. The value R Square shows that 62,9% of the consumer purchase interest variable can be explained by the variables of social media and product quality. While the rest 37,1% is explained by different variables not tasted with this study.